Taboo or not taboo : sexuality and family in the Hebrew Bible - Rashkow, Ilona N. (Ilona Nemesnyik) (Minneapolis : Fortress Press, 2000)
"Rashkow's analysis provides a reflection on family, which is given texture and depth through her use of psychoanalysis and literary theory. And her use of comparative ancient Near Eastern materials provides a fresh vantage point from which to evaluate Israel's epic stories."--Jacket.
1. Psychoanalytic Literary Theory and the Hebrew Bible: What Hath Freud Wrought? -- 2. Sin and Sex, Sex and Sin: The Hebrew Bible and Human Sexuality -- 3. Throw Momma from the Garden a Kiss: Or Paradise Revisited -- 4. Oedipus Wrecks: The Covenant of Circumcision -- 5. Daddy-Dearest and the "Invisible Spirit of Wine": Theme and Variations -- 6. Boys Will Be Boys: Sibling Rivalry and the Fear of Castration -- 7. My Sister, My-Hmmm ... : Brother-Sister Incest and Sibling Rivalry.
Includes bibliographical references (pages 173-182) and indexes.
Keywords: Bible. -- Psychology; Dysfunctional families in the Bible; Sex in the Bible; Psychoanalysis and religion; Sex -- Religious aspects; Psychoanalysis -- folklore, mythology, & religion; Psychology -- in folklore, mythology, & religion; Family -- in folklore, mythology, & religion; Religion and Sex